1987
DOI: 10.1017/s0079497x00006204
|View full text |Cite
|
Sign up to set email alerts
|

Excavations at Hog Cliff Hill, Maiden Newton, Dorset

Abstract: A segment of earlier Bronze Age arable landscape incorporating isolated round barrows on the high chalk spur of Hog Cliff Hill became the chosen location for a later Bronze Age earthwork of considerable dimensions. The area excavated within the bank and ditch was densely occupied by two major phases of buildings of timber construction, lasting into the earliest Iron Age. Sometime during the early Iron Age the oval enclosure was replaced by a more substantial one which partly followed its line and contained a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Characterization studies may reveal subtle variation not apparent macroscopically, as occurred at one hillfort in south-west England, Norton Fitzwarren (Woodward 1989), and three settlements in central-southern England, Hog Cliff Hill (Ellison & Williams 1987), Potterne (Morris 1991a) and Old Down Farm (Wandibba 1981). Petrological analysis of the Norton Fitzwarren assemblage revealed a dramatic discovery Hamilton 1968Hamilton 1956Rigby 1986Brewster 1963Savory 1971Morris 1983aGuilbert 1976Morris 1983aChowne 1980Jackson & Knight 1985Farley & Knight 1986Morris 1991bHamilton 1982Hamilton 1980O'Connell 1986Williams 1984Brown 1988Barrett 1978DeRoche 1978Wainwright 1970Marshall 1989Dixon 1976Saville 1984Cunliffe & Phillipson 1968Lambrick 1979Morris 1987aEllison 1982Brown 1991bFell 1961Saville 1984Alcock 1980Russell 1989Mytum 1986 -approximately 50-60% of the assemblage dated to c. 900-400 BC was made from an igneous rock-gritted fabric, for which the closest geological source is 45 km away.…”
Section: Earliest-early Iron Agementioning
confidence: 99%
See 1 more Smart Citation
“…Characterization studies may reveal subtle variation not apparent macroscopically, as occurred at one hillfort in south-west England, Norton Fitzwarren (Woodward 1989), and three settlements in central-southern England, Hog Cliff Hill (Ellison & Williams 1987), Potterne (Morris 1991a) and Old Down Farm (Wandibba 1981). Petrological analysis of the Norton Fitzwarren assemblage revealed a dramatic discovery Hamilton 1968Hamilton 1956Rigby 1986Brewster 1963Savory 1971Morris 1983aGuilbert 1976Morris 1983aChowne 1980Jackson & Knight 1985Farley & Knight 1986Morris 1991bHamilton 1982Hamilton 1980O'Connell 1986Williams 1984Brown 1988Barrett 1978DeRoche 1978Wainwright 1970Marshall 1989Dixon 1976Saville 1984Cunliffe & Phillipson 1968Lambrick 1979Morris 1987aEllison 1982Brown 1991bFell 1961Saville 1984Alcock 1980Russell 1989Mytum 1986 -approximately 50-60% of the assemblage dated to c. 900-400 BC was made from an igneous rock-gritted fabric, for which the closest geological source is 45 km away.…”
Section: Earliest-early Iron Agementioning
confidence: 99%
“…There is consistent evidence in some parts of the country, such as the Wessex area of central-southern England, for a very limited amount of non-local production and intraregional distribution (Champion 1986, 30;Williams 1987, 251). Analysis of red-finished, or 'haematitecoated', pottery has demonstrated that the vessels were produced in a variety of locations: 1) both in the local vicinity and further afield (Gale L979, 51-53;Davies 1981, 108); 2) locally (Partridge 1974;Ellison & Williams 1987); or 3) as in the case of a very distinctive type of extremely fine fabric 'scratched-cordoned' bowls dated to the very end of the Early Iron Age (c. 6th~5th century BC), at a single concentrated location, and then distributed to sites up to 40 km away from the resource zone (Cunliffe 1984a, 255;1984b, fig. 2.8).…”
Section: Earliest-early Iron Agementioning
confidence: 99%